Plant availability of two phosphate rock materials in acid Malaysian soils - Hanafi, M.M.; Syers, J.K. (1994)
The amount of phosphorus (P) dissolved in a closed-incubation system, in soils receiving Christmas Island grade-A phosphate rock (CIPR), Gafsa phosphate rock (GPR), and triple superphosphate (TSP), as measured by extraction with 0.5M NaHC03 (ΔPb) or 0.5M NaOH (AP) and expressed as ΔPb/ΔP*100 (PDP) was compared to P uptake (ΔPs) by Setaria in a glasshouse experiment. There was no direct relationship between ΔPs and PDP for CIPR, GPR, and TSP added at 50 and 150 mgP/kg soil to three Malaysian soils (Bungor, Kundor, and Segamat) during a 10-month period. Averaged across soils, rate of addition, and P sources, ΔPs was 17% higher than PDP. Overestimation of PDP by ΔPs could be due to the ability of the roots of Setaria to use more of the P which is dissolved from the three P sources and then chemisorbed, than can be extracted by the NaHC03 reagent. The chemisorbed P pool is extractable using 0.5M NaOH. There was a close relationship between ΔPs and AP, with a correlation coefficient of 0.85*. Residual P, determined by Pb method after each harvest, successfully predicted Ps by Setaria in the subsequent harvest with correlation coefficients varying between 0.74* and 0.99** for CIPR, GPR, and TSP in five soils (Bungor, Durian, Kundor, Segamat, and Tok Yong). The critical Pb values ranged from 5 for Durian to 10 mgP/kg soil for Kundor.